Implementation of Islamic Religious Education Lessons in Instilling Religious Character in Children on the Autism Spectrum at Semesta Mandiri School - Veronica, Anggie (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to examine the implementation of Islamic Religious Education (PAI) lessons in instilling religious character in children with autism spectrum disorder. The subjects of the study consist of students with autism spectrum disorder who are participating in PAI lessons at Semesta Mandiri Sunggal School. The research method used is descriptive qualitative with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed using thematic analysis techniques. The results of the study indicate that the implementation of PAI lessons for children with autism spectrum disorder requires a different approach compared to typical children. The approaches used include adjusting the teaching materials, using engaging learning media, and employing interactive teaching methods. Additionally, the role of PAI teachers is very important in providing guidance and motivation to students. Through PAI lessons, children with autism spectrum disorder show development in aspects of religious character, such as increased awareness of worship, understanding of religious values, and more positive social behavior. In conclusion, the structured and adaptive implementation of PAI lessons can be effective in instilling religious character in children with autism spectrum disorder. This research recommends special training for PAI teachers in managing learning for autistic students, as well as support from parents and the school environment to achieve optimal results.